Conspiracy Mongering in Venezuela: The Chavismo Period (1998–2018). (6th September 2019) - Andrade, Gabriel
Abstract : Hugo Chávez's rise to power in 1998 brought many changes to Venezuela's political culture. One transformation not frequently commented on is the constant formulation of conspiracy theories, both by chavismo supporters and by its opponents. This article discusses some of those conspiracy theories, relating to the deceased Venezuelan President's origins, his religious beliefs, the 2002 failed coup d'état, and Chávez's own death. It also addresses more recent conspiracy theories relating to Nicolás Maduro's birth, economic warfare, and drug smuggling operations. Venezuela is currently undergoing a major humanitarian crisis, and this article defends the view that, at least partially, conspiracy mongering has been a factor in Venezuela's collapse. As part of Venezuela's reconstruction, this article recommends that Venezuelan political forces need to reach a consensus and agree not to make ridiculous conspiratorial claims.